Sepsis in frail patient - Andrea Beltrame; Emanuele Nadir Malfatto; Marco Anselmo (Italian Journal of Medicine, 2016)
Frailty is defined as a clinical syndrome in which three or more of the following criteria are present: unintentional weight loss, self-reported exhaustion, weakness (grip strength), slow walking speed and low physical activity. Sepsis is defined as an inflammatory response to infection, with severe sepsis and septic shock being the most severe forms. The incidence of severe sepsis increases with older age and several studies have shown that there are many risk factors that predispose the elderly to a higher incidence of sepsis. Pre-existing co-morbidities such as cancer, diabetes, obesity, human immunodeficiency virus, and renal or pulmonary disease can cause sepsis, but other factors including poor lifestyle habits (i.e., smoking, drug or alcohol abuse), malnutrition, and endocrine deficiencies, which are frequent in the elderly, may also predispose to severe infections. Other risk factors for sepsis include recurrent hospitalization, especially in the Intensive Care Unit, and nursing home residence, where interventions such as urinary catheterization or multiple drug use are quite frequent and many studies reported that people above 65 years of age are three times more likely to be admitted to hospital than those aged 16-64 years, and have a higher risk of prolonged hospital stays, institutionalization and death. Clinical evaluation of the frail patient with sepsis poses some challenges. The immune response becomes progressively less efficient with increasing age thereby causing an altered response to infection and it is important to know that the clinical evaluation of the so-called fragile patient with severe infection should take into account the sometimes unusual signs and symptoms that, if identified, can lead to early diagnosis. Laboratory diagnostics can also be of great help in this setting. The treatment of sepsis in the fragile patient can be empirical or based on microbiological culture. Moreover, frail patient population presents many clinical problems with numerous comorbidities, therefore anti-infective treatment is difficult, so the physician’s armamentarium must include many antibiotic drugs, of which there are far more available for the treatment of sepsis caused by Gram-positive bacteria than for sepsis caused by Gram-negative ones or fungi.